The Role of Islamic Social Finance Through Ziswaf and BMT During The Covid-19 Pandemic - Purwanto Purwanto; Fitri Nurba Sari; Mona Burasukma; Siti Nursolihah (IAIN Kudus, 2021)
This research was conducted to explain the role of Islamic social finance through ZISWAF and BMT during the Covid-19 pandemic. This study uses qualitative methods that use library research techniques. The results of the study indicate that Islamic social finance plays an important role in dealing with declining economic conditions during the Covid-19 pandemic. The existence of ZISWAF can reduce the problem of poverty due to the Covid-19 pandemic, as well as the existence of BMT which can encourage businesses that lack capital and of course can help the government in dealing with existing problems. The role of Islamic social finance is shown by offering solutions to overcome economic problems, namely: the distribution of BLT originating from zakat collection units or from people with more income, assistance in the form of zakat, infaq, or alms; increasing waqf with cash waqf schemes, productive waqf or waqf linked sukuk waqf in order to strengthen waqf; assistance in the form of business capital to Micro, Small and Medium Enterprises (UMKM) groups experiencing crisis conditions; providing venture capital followed by a qardhul hasan loan scheme; providing understanding to increase literacy related to sharia economics and finance; sharia financial technology development. The implication is to help the welfare of the poor so that they become more capable people by providing business capital.